Pseudonocardia thailandensis sp. Nov., an actinomycete isolated from a subterranean termite nest - Kanaporn Sujarit (2018)
© 2017 IUMS. A novel Gram-stain-positive bacterium designated CMU-NKS-70 T was isolated from a subterranean termite nest and characterized using a polyphasic approach. The strain exhibited branching, pinkish-cream aerial mycelium and cream-brown substrate mycelium, and formed chains of rod-like spores. The 16S rRNA gene sequence analyses indicated that strain CMU-NKS-70 T belonged to the genus Pseudonocardia, showing high similarity with Pseudonocardia oroxyli D10 T (98.9 % 16S rRNA gene sequence similarity), Pseudonocardia xishanensis YIM 63638 T (98.9 %) and Pseudonocardia kujensis A4038 T (98.5 %). However, DNA-DNA relatedness values between strains CMU-NKS-70 T and the closest phylogenetically related species ranged from 40.5±2.9 to 48.6±0.7 %. Whole-cell hydrolysates of strain CMU-NKS-70 T consisted of meso-diaminopimelic acid, glucose, galactose, arabinose, mannose, ribose and rhamnose. The predominant menaquinone was MK-8(H4). The major cellular fatty acids ( > 10 %) were iso-C 16 : 0 , C 16 : 0 , C 16 : 1 ω7c and/or iso-C 15 : 0 2-OH and 10-methyl C 16 : 0 . The polar lipids detected were phosphatidylethanolamine, phosphatidylmethylethanolamine, hydroxyphosphatidylethanolamine, phosphatidylglycerol, phosphatidylinositol, three unidentified glycolipids and two unidentified phospholipids. The G+C content of genomic DNA was 71.9 mol%. The physiological and biochemical properties also supported the phenotypic distinction of strain CMU-NKS-70 T from its closely related species. On the basis of evidence from this study using a polyphasic approach, strain CMU-NKS-70 T represents a novel species of the genus Pseudonocardia for which the name Pseudonocardia thailandensis sp. nov. is proposed. The type strain is CMU-NKS-70 T (=JCM 31292 T =TBRC 2000 T ).